Evaluation of the first two Frontline cohorts of the field epidemiology training program in Guinea, West Africa - Doreen Collins; Boubacar Ibrahima Diallo; Mariama Boubacar Bah; Marlyatou Bah; Claire J. Standley; Salomon Corvil; Lise D. Martel; Pia D. M. MacDonald (BMC, 2022)
Abstract Background The 2014-2016 Ebola virus disease outbreak in West Africa revealed weaknesses in the health systems of the three most heavily affected countries, including a shortage of public health professionals at the local level trained in surveillance and outbreak investigation. In response, the Frontline Field Epidemiology Training Program (FETP) was created by CDC in 2015 as a 3-month, accelerated training program in field epidemiology that specifically targets the district level. In Guinea, the first two FETP-Frontline cohorts were held from January to May, and from June to September 2017. Here, we report the results of a cross-sectional evaluation of these first two cohorts of FETP-Frontline in Guinea. Methods The evaluation was conducted in April 2018 and consisted of interviews with graduates, their supervisors, and directors of nearby health facilities, as well as direct observation of data reports and surveillance tools at health facilities. Interviews and site visits were conducted using standardized questionnaires and checklists. Qualitative data were coded under common themes and analyzed using descriptive statistics. Results The evaluation revealed a significant perception of improvement in all assessed skills by the graduates, as well as high levels of self-reported involvement in key activities related to data collection, analysis, and reporting. Supervisors highlighted improvements to systematic and quality case and summary reporting as key benefits of the FETP-Frontline program. At the health facility level, staff reported the training had resulted in improvements to information sharing and case notifications. Reported barriers included lack of transportation, available support personnel, and other resources. Graduates and supervisors both emphasized the importance of continued and additional training to solidify and retain skills. Conclusions The evaluation demonstrated a strongly positive perceived benefit of the FETP-Frontline training on the professional activities of graduates as well as the overall surveillance system. However, efforts are needed to ensure greater gender equity and to recruit more junior trainee candidates for future cohorts. Moreover, although improvements to the surveillance system were observed concurrent with the completion of the two cohorts, the evaluation was not designed to directly measure impact on surveillance or response functions. Combined with the rapid implementation of FETP-Frontline around the world, this suggests an opportunity to develop standardized evaluation toolkits, which could incorporate metrics that would directly assess the impact of equitable field epidemiology workforce development on countries' abilities to prevent, detect, and respond to public health threats.